Design of Sipiso-Piso resort Hotel with “Neo Vernacular Architecture Approach” In Karo - Firman Eddy; Yuni An Sari Nasution (Talenta Publisher, 2018)
Tourism is a very important sector in a country because it can improve the economy. Tourism is able to contribute greatly to the addition of foreign exchange that can be utilized for the development and prosperity of the people for developing countries like Indonesia. Tourism development in Karo Regency especially Sipiso-Piso Waterfall is very important to be developed because it has the potential that is not inferior to other tourist destination in Indonesia. The existing potential can be utilized optimally to reach the destination as the main tourist attractions so that the tourism sector becomes a source or supplier of strategic funds in supporting the development of the Karo Regency. The Hotel resort is the best solution in developing Sipiso-Piso Waterfall object. In order for tourism potential to develop and serve as a reliable product sold in the global market, this design can be done using Neo Vernacular Architecture approach to raise the local culture in Indonesia, especially the existing culture in Karo and Lake Toba.